Cultivating Disciplinary Character Through Structured Assignment Management: A Comparative Case Study in Elementary Education - Dwi Wiyanti; Ade Tutty R Rosa (Journal of Innovation and Research in Primary Education, 2026)
Discipline formation in elementary education faces challenges from inadequate instructional planning, limited parental involvement, and adverse socioeconomic conditions. This study examines the effectiveness of structured assignment management through the POAC (Planning, Organizing, Actuating, Controlling) framework in cultivating disciplinary character among elementary students.  A qualitative case study was conducted at two elementary schools in West Jakarta involving school principals (n=2), teachers (n=8), and students (n=24). Data were collected through semi-structured interviews, systematic observations, and documentary analysis, then analyzed inductively with triangulation procedures to ensure credibility. Findings revealed significant implementation variations between schools. Comprehensive POAC application—characterized by systematic planning, coordinated organization, consistent execution, and rigorous evaluation—effectively enhanced student discipline, manifested through improved assignment completion rates, punctuality, and rule compliance. Conversely, partial implementation yielded suboptimal outcomes. Unexpectedly, institutional support mechanisms partially compensated for socioeconomic disadvantages when systematically delivered.  Structured assignment management operationalized through POAC constitutes an effective strategy for disciplinary character development, with implementation fidelity determining intervention success. Findings contribute empirical evidence bridging educational management theory and character education practice, informing policy regarding resource allocation, professional development, and family-school partnerships necessary for sustained disciplinary cultivation.